Integrating the Saemaul Undong Spirit: Stimulating Capacity for Rural Development - Samson-Gaddi, Rebecca; Park, Seung Woo; Lee, Kwang Dong (Philippine Journal of Labor and Industrial Relations; Vol 35 (2018): Philippine Journal of Labor and Industrial Relations, 2021)
This article is a narrative of DALUYONG, a national women organization where the leadership, while nearly in a demising fieriness, exhibited behavioral and attitudinal change after some exposure to South Korea’s rural development approach and experiences. After which, we were able to validate the feasibility of integrating two rural development frameworks and experiences (Philippines and South Korea), through the ‘four-fold approach plus one’ of the Philippine Rural Reconstruction Movement (PRRM) and ‘spirits of Saemaul Undong’- the key to South Korea’s successful and fast industrial growth.